The Environmental Aspect of Companies as a Determinant of Stock Prices - Ida Nurcahyanti; Purweni Widhianningrum (Universitas PGRI Madiun, 2018)
This study aims to determine the effect of disclosure of Corporate Social Responsibility which is composed of economic, environmental and social to the stock price on the companies listed on the Indonesia Stock Exchange. The analysis technique uses multiple regression. The results of this study indicate that the economic and social aspects of Corporate Social Responsibility disclosure does not affect the stock price, while the environmental aspects affect the stock price. These results prove that companies that have environmental concerns as an effort to reduce the effects of global warming, can also increase the positive response of stakeholders through an increase in stock prices.